2020
DOI: 10.1108/jhass-07-2020-0093
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of the push factors of human capital flight in Nigeria

Abstract: Purpose Human capital flight from Nigeria to developed countries has remained a topical issue. This paper aims to empirically analyze the push factors for the migrants who explore the various legal migrant schemes from a macro perspective. The authors examine human capital development and its role in contributing to human capital flight to more developed counties. Design/methodology/approach This paper is anchored on the push–pull model. Using secondary data from 1990 to 2019, the authors look at the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…On the other hand, Vecchione (2018) focused on the Italian economy and found that high skilled migration drastically reduced human capital accumulation in Italy The findings showed that migration negatively impacted human capital development. These findings imply that the problem of human development may be a cause and effect of human capital flight as revealed by Tabassum et al (2017), Adeosun and Popogbe (2020); and Popogbe and Adeosun (2020). The study by Docquier and Rapoport (2012) further revealed that uncontrolled high-skilled migration led to a shortage of health workers in Sub-Saharan Africa in 2010, which, in turn, led to worsened health status.…”
Section: Human Capital Flight and Output Growthmentioning
confidence: 80%
See 3 more Smart Citations
“…On the other hand, Vecchione (2018) focused on the Italian economy and found that high skilled migration drastically reduced human capital accumulation in Italy The findings showed that migration negatively impacted human capital development. These findings imply that the problem of human development may be a cause and effect of human capital flight as revealed by Tabassum et al (2017), Adeosun and Popogbe (2020); and Popogbe and Adeosun (2020). The study by Docquier and Rapoport (2012) further revealed that uncontrolled high-skilled migration led to a shortage of health workers in Sub-Saharan Africa in 2010, which, in turn, led to worsened health status.…”
Section: Human Capital Flight and Output Growthmentioning
confidence: 80%
“…However, the study by Popogbe and Adeosun (2020) revealed that increased population growth rate and poor life expectancy increases the likelihood of migrating out of Nigeria. Indeed, Adeosun and Popogbe (2020) affirmed that the increasing population has always been to the disadvantage of the Nigerian economy.…”
Section: Human Capital Flight and Output Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Such mobility has been less examined when considering the establishment of permanent residence of such scientific workforce in advanced countries (long-term immigration) as opposed to quick schemes of mobility (i.e., participation in training and short-term educational programs). As the global competition to attract highly educated individuals has intensified, the emergence of phenomena, known as “brain drain” (Durmaz, 2020 ), “human capital flight” (Popogbe and Oluyemi, 2020 ), and “academic exodus” (Heffernan and Heffernan, 2020 ), has dominated the literature. These concepts assume the loss of talented and outstanding professionals who flee from one country or region (developing) instead of another (developed).…”
Section: Introductionmentioning
confidence: 99%